Sistem Monitoring Listrik Tiga Phasa Berbasis Panel LED P10 - suwanda, ivan (Indonesian Society of Applied Science (ISAS), 2024)
Abstract The increasing demand for electricity consumption monitoring in various sectors, including educational environments, requires an accurate, efficient, and real-time monitoring system. This study aims to design and develop a three-phase electricity monitoring system using a P10 LED Matrix panel controlled by an Arduino Mega microcontroller. The system is designed to display voltage, current, and frequency parameters directly through the LED panel, replacing conventional LCD displays with limited size and visibility. The design methodology includes problem identification, data collection through literature study and observation, hardware and software design, assembly, and system testing. The main components consist of three PZEM-004T sensors for electrical data acquisition, an Arduino Mega ATmega2560 as the processing unit, and three P10 LED Matrix panels as the visualization medium. Testing results show that the system can display real-time data with high accuracy. The average voltage measurement error was 0.0013%, and the current measurement error was 0.057%, both well below the 0.5% tolerance specified by the sensor. This system has proven reliable for monitoring three-phase electrical loads at the Politeknik Negeri Ketapang Laboratory Building. In conclusion, the developed system can enhance electricity monitoring efficiency, facilitate electrical condition analysis, and has the potential for further development by integrating Internet of Things (IoT) technology for remote monitoring. Keywords: Electrical monitoring system, three-phase, P10 LED panel, Arduino Mega, PZEM-004T.